Investigation of Parametric Performance of the Hybrid 3D CPC/TEM System Due to Thermoelectric Irreversibilities - Mgbemene, Chigbo Aghaegbusi; Njoku, Howard Okezie; Agbo, Cornelius Ogbodo Anayo (Frontiers in Energy Research, 2018)
The effects of the device performance parameter, denoted as ψ, due to thermoelectric irreversibilities on the hybrid compound parabolic concentrator and the thermoelectric module (3D CPC/TEM) system for power generation, have been investigated. The dependence of the behavior of the parameter on the thermoelectric irreversibilities is highlighted. The paper shows that when ψ is plotted against the collector thermal efficiency, a linearized plot is obtained. When plotted against the other system's output parameters, the resulting plots exponentially decay. The plots could be used for determining the desirable range for good performance of the system. The linearized plot could be useful in the determination of the values of the receiver plate temperature and the heat loss from the collector.